Improving Teachers' Understanding and Readiness in Implementing STEM through Science Learning Simulation (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study expects to discover the improvement of science teachers' comprehension of the STEM concept, the improvement of teachers' readiness in implementing it, and the relationship between the comprehension of STEM concepts and readiness in implementing it in learning science. The participants were 50 science teachers from a few junior high schools in Ciamis who joined the workshop and simulated natural science learning dependent on STEM concepts in the Galuh University in Ciamis, Indonesia. The method of study used descriptive utilizing instruments of questionnaires and interview guide. The data were investigated using descriptive statistics with SPSS version 25.0. In addition, data from interviews were analyzed qualitatively (as complementary data). The exploration results show an increase in understanding of the STEM concept of science teachers and an increase in teacher readiness to implement it in science learning. This increase in understanding of STEM concepts and readiness to implement them is strengthened by developing a plan for implementing STEM-based learning and observing STEM-based science learning simulation activities conducted by several workshop participants. In addition, there is also a high correlation between understanding the STEM concept and the teacher's readiness to implement it in science learning.